Radiation field creation at the electron linac LUE-10 for long-term tests of structural materials under molten-salt reactor conditions - Dovbnya, A.N.; Zykov, A.I.; Zlunitsyn, Eh.S.; Torgovkin, A.V.; Shramenko, B.I. (Вопросы атомной науки и техники, 2006)
Long-term (700 hours) corrosion tests of hastelloy-type alloy samples were performed in the ZrF4+NaF melt at a
temperature of 650°C with the use of the electron linac LUE-10 of power of about 5 kW. To reduce the residual radioactivity
of irradiated materials, studies were made into possible ways of a smooth energy shift at the maximum of
the electron spectrum to the lower energy region under conditions of a strong current load. На ускорителе электронов ЛУЭ-10 с мощностью ≅ 5 кВт проведены долговременные (700 часов) испытания коррозионной стойкости образцов сплава типа Хастеллой Н в расплаве солей ZrF4+NaF при температуре 650оС. С целью снижения остаточной радиоактивности облучаемых материалов в условиях сильной подгрузки током изучены возможности плавного сдвига энергии в максимуме спектра электронов в низкоэнергетическую область. На прискорювачі електронів ЛПЕ-10 з потужністю ≅5 кВт проведено довготривалі (700 годин)
випробування корозійної стійкості зразків сплаву типу Хастелой Н у розплаві солей ZrF4+NaF при
температурі 650оС. З метою зниження залишкової радіоактивності опромінених матеріалів в умовах
сильного навантаження струмом. вивчено можливості плавного здвигу енергії в максимумі спектру
електронів в низькоенергетичну область.